United States, sign along road in Fairbanks - Sorensen, Clarence Woodrow, 1907-1982; Harris, Eugene V., 1913-1978 (1934)
Sign on fence at intersection for Yukon Plumbing Supplies. Grayscale Sorensen Safety Negatives, Binder: North & Central America 3